Waterpipe smoking in students: Prevalence, risk factors, symptoms of addiction, and smoke intake. Evidence from one British university - Jackson, D; Aveyard, P (BioMed Central, 2008)
Background: Anecdotal reports suggest waterpipe smoking is becoming common in students in western countries. The aim was to examine prevalence, risk factors, symptoms of addiction, and smoke intake. Methods: This was a cross-sectional survey of students with subsidiary survey of regular waterpipe user and survey of exhaled carbon monoxide (CO) before and after waterpipe smoking in customers of a waterpipe café. 937 students of Birmingham University completed the initial survey with a follow up of 21 regular waterpipe smokers. 63 customers of a waterpipe café near the University completed the study of CO intake. Results: 355 (37.9%, 95% confidence intervals (CI) 34.8 to 41.1%) students had tried waterpipes, the prevalence of trying rising with duration at University. 75 (8.0%, 95%CI 6.4 to 10.0%) were regular smokers, similar to the prevalence of cigarette smoking (9.4%). Although cigarette smoking was the major risk factor for being a regular waterpipe smoker, odds ratio (95%CI) 2.77 (1.52 to 5.06), 65% of waterpipe smokers did not smoke cigarettes. Seven of 21 (33.3%) regular waterpipe smokers experienced cravings. Nearly all regular waterpipe users thought it less harmful than smoking cigarettes. The mean (standard deviation) rise in CO was 37.4 (25.8)ppm, nearly twice as high as a typical cigarette smoker seeking cessation treatment. Conclusion: Waterpipe smoking is a common part of student culture in one British university, as in the Middle East and in the United States. It poses a potential threat to public health, with evidence of dependence and high smoke intake.